2012
DOI: 10.1007/s10815-012-9743-9
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproduction outcomes after embryo transfers requiring a malleable stylet

Abstract: Objective This retrospective case-control study was undertaken to assess the impact of a malleable stylet application on embryo transfer (ET) outcome. Methods The Wallace malleable stylet was used when the soft inner catheter could not negotiate the internal os during ultrasound-guided ET. Patients having an age ≤37 years, with three embryos replaced were included in the analysis. Implantation rate, clinical pregnancy rate and live birth rate were the main outcome measures. Results The Wallace malleable stylet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Italian legislation requires that embryo production must not exceed what is strictly necessary based on individual patient characteristics. Embryos were classified into types A, B, and C according to the following morphological characteristics (Tiboni et al, 2012): type A or excellent embryos composed with regular blastomeres with equal or nonequal size without fragmentation; type B or good embryos with blastomeres of equal or non-equal size with < of 20% of the embryo volume with enucleate fragments; and type C or fair embryos with anucleate fragments in 20-50% of the volume of the embryo.…”
Section: Gcs Isolation and In Vitro Fertilizationmentioning
confidence: 99%
“…Italian legislation requires that embryo production must not exceed what is strictly necessary based on individual patient characteristics. Embryos were classified into types A, B, and C according to the following morphological characteristics (Tiboni et al, 2012): type A or excellent embryos composed with regular blastomeres with equal or nonequal size without fragmentation; type B or good embryos with blastomeres of equal or non-equal size with < of 20% of the embryo volume with enucleate fragments; and type C or fair embryos with anucleate fragments in 20-50% of the volume of the embryo.…”
Section: Gcs Isolation and In Vitro Fertilizationmentioning
confidence: 99%
“…Sloppy practices and imprecise placement of the transferred embryos in the uterine cavity undermine the good clinical and biological work that came together to obtain these embryos. 255 Interestingly, it is the very person who first conceived oocyte retrieval under ultrasound guidance 256 who was the first to advocate in 1987 for ultrasound-directed embryo transfers. 4 In 1991, a prospective trial reported higher pregnancy rates in 94 women who had an ultrasound-guided transfer as compared to 246 controls who had the classical approach.…”
Section: Embryo Transfersmentioning
confidence: 99%